Effect of chronic hepatitis C virus infection on inflammatory lipid mediators - Guerra, Cristina Tosti; Caini, Patrizio; Giannini, Carlo; Giannelli, Francesca; Gragnani, Laura; Petrarca, Antonio; Solazzo, Vera; Monti, Monica; Laffi, Giacomo; Zignego, Anna Linda (Digestive and liver disease, 2007)
Platelet-activating factor (PAF), a powerful phospholipid mediator of inflammation, is degraded by plasma PAF-acetyl-hydxolase (pPAF-AH), an enzyme which circulates in serum mainly in a complex with lipoproteins that confer its biological activity. Hepatitis C virus (HCV) is linked to lipoproteins in serum too. Reduced pPAF-AH activity was observed in several diseases, including systemic vasculitis. To evaluate if chronic HCV infection could alter pPAF-AH physiological functions. 145 subjects were studied: 56 HCV- and 52 HBV-infected patients (pathologic controls); 37 healthy subjects (healthy controls). pPAF-AH activity, PAF and Apo B100 titers were determined in plasma; enzyme expression levels were evaluated in monocyte-derived macrophages. HCV-RNA was detected in plasma, peripheral blood mononuclear cells and liver samples. HCV-infected patients showed an increase of PAF levels following a significant decrease of pPAF-AH activity. A recovery of pPAF-AH activity occurs only in patients who clear HCV after the antiviral treatment. Expression levels of pPAF-AH mRNA and Apo B100 titers were not modified in HCV patients in comparison to controls. In light of these results, it is tempting to hypothesize that during chronic HCV infection, the PAF/pPAF-AH system may be altered and this condition may contribute to HCV-related vascular damage.